The Polish sentence test for speech intelligibility evaluations - Ozimek, E.; Kutzner, D.; Sęk, A.; Wicher, A.; Szczepaniak, O. (Archives of Acoustics, 2006)
The main purpose of this study was to prepare Polish sentence tests for measuring speechintelligibility against an interfering noise. The tests were developed from meaningful sentencestaken from everyday utterances, TV, literature etc. Two sets of sentence lists werecreated. The first set was optimized for the so-called binary scoring and was composed of25 lists of 20 sentences each, while the second set was prepared for word-based scoring andwas composed of 22 lists of 20 sentences each. The respective lists were statistically andphonemically balanced, i.e. they produced comparable psychometric functions and revealedcomparable phonemic distribution. The mean SRT (Speech Reception Threshold) and $S_{50}$(slope of a psychometric function at the SRT point) were: −6.1 dB and 29.5%/dB for thebinary scoring and −7.4 dB and 26.7%/dB for the word-based scoring, respectively. The testlists comply with the requirements of the high quality test for measuring speech intelligibilityof the Polish language.